Coordination and variability in the elite female tennis serve - Whiteside, D.; Elliott, B. C.; Lay, B.; Reid, M. (Journal of Sports Sciences, 2015)
Enhancing the understanding of coordination and variability in the tennis serve may be of interest to coaches as they work with players to improve performance. The current study examined coordinated joint rotations and variability in the lower limbs, trunk, serving arm and ball location in the elite female tennis serve. Pre-pubescent, pubescent and adult players performed maximal effort flat serves while a 22-camera 500 Hz motion analysis system captured three-dimensional body kinematics. Coordinated joint rotations in the lower limbs and trunk appeared most consistent at the time players left the ground, suggesting that they coordinate the proximal elements of the kinematic chain to ensure that they leave the ground at a consistent time, in a consistent posture. Variability in the two degrees of freedom at the elbow became significantly greater closer to impact in adults, possibly illustrating the mechanical adjustments (compensation) these players employed to manage the changing impact location from serve to serve. Despite the variable ball toss, the temporal composition of the serve was highly consistent and supports previous assertions that players use the location of the ball to regulate their movement. Future work should consider these associations in other populations, while coaches may use the current findings to improve female serve performance.